2012
DOI: 10.1111/j.1747-1567.2012.00845.x
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of Multi-damage Detection in a Plate Based on Non-modal Method

Abstract: Many published damage localization indices require structural modal identification and mathematical model of the undamaged structure. However, it is somewhat inconvenient for use in practical engineering. In this study, an efficient localization index has been presented, named as image flexibility of frequency response function, for damage detection in plate‐like structures. In order to avoid the finite element model error, two‐dimensional gapped smoothing method is employed without the need for the baseline d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Ratcliffe and Bagaria [71] successfully employed the GSM to locate a manufactured delamination in a small-scale glass-reinforced epoxy beam. The GSM approach was extended to two-dimensional structures, such as plates [21,[74][75][76], using a cubic polynomial with two variables to represent curvature of the plate. Subtracting the fitted curvature of the undamaged state from the calculated curvature of the damaged state of plates resulted in peaks at the damaged locations.…”
Section: Review Of Space Domain-based Techniques Using the Curve-fitt...mentioning
confidence: 99%
See 2 more Smart Citations
“…Ratcliffe and Bagaria [71] successfully employed the GSM to locate a manufactured delamination in a small-scale glass-reinforced epoxy beam. The GSM approach was extended to two-dimensional structures, such as plates [21,[74][75][76], using a cubic polynomial with two variables to represent curvature of the plate. Subtracting the fitted curvature of the undamaged state from the calculated curvature of the damaged state of plates resulted in peaks at the damaged locations.…”
Section: Review Of Space Domain-based Techniques Using the Curve-fitt...mentioning
confidence: 99%
“…Recognizing these limitations, Gao et al [75,76] proposed a non-modal damage localization technique utilizing frequency response functions (FRF) [83] combined with a two-dimensional GSM to detect and localize damage in plate-like structures. Unlike mode shapes and their derivatives that were based on natural frequencies, the FRF shapes and their derivatives were based on a wide range of frequencies; hence, provided more information on the location of damage.…”
Section: Review Of Space Domain-based Techniques Using the Curve-fitt...mentioning
confidence: 99%
See 1 more Smart Citation
“…It is difficult to obtain the baseline data due to the difference between the numerical simulation and the actual structure. Gao et al [21] employed two-dimensional GSM (Gapped Smoothing Method) with statistical noise suppression. Experimental study on the steel plate demonstrated the effectiveness of the proposed index.…”
Section: Introductionmentioning
confidence: 99%
“…On the base of the authors' previous research [7], a novel efficient damage localization index from FRFs is formulated in this paper. For carrying out multi-damage localization in plate structures, two-dimensional gapped smoothing method (GSM) is employed.…”
Section: Introductionmentioning
confidence: 99%